2003
DOI: 10.3727/000000003783985214
|View full text |Cite
|
Sign up to set email alerts
|

Areal Density Measurement is a Convenient Method for the Determination of Porcine Islet Equivalents without Counting and Sizing Individual Islets

Abstract: The determination of islet mass is important for the normalization of islet experiments in the laboratory and for the precise dosing of islets for transplantation. The common microscopical analysis is based on individual islet sizing, calculation of the frequency distribution, and conversion into islet equivalents (IEQ), which is the volume of a spherical islet with a diameter of 150 µm. However, islets are of irregular form, which makes this determination user dependent, and the analysis is irreproducible onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
0
20
2
Order By: Relevance
“…5 Top and side views of the scaffold designed to accommodate~33,000 porcine islet equivalents with~35% solids in the suspension (Lembert et al 2003).…”
Section: Side Viewmentioning
confidence: 99%
“…5 Top and side views of the scaffold designed to accommodate~33,000 porcine islet equivalents with~35% solids in the suspension (Lembert et al 2003).…”
Section: Side Viewmentioning
confidence: 99%
“…Recently, Friberg et al (2) reported a different DIA system that allows for reduced variability of islet count compared to manual counting methods. Although, many other DIA systems have been tested previously, shortcomings affecting accuracy of the results existed in these studies (1, 2, 3, 4, 6, 7, 10, Hui Jian Zhang, University of Minnesota-personal communication,). Among the issues was that although islet samples stained with DTZ were manually counted immediately, the images might have been taken hours later or even on the following day.…”
Section: Introductionmentioning
confidence: 99%
“…As islets from WT and PPARE Ϫ / Ϫ mice varied in diameter, we hand-picked islets under a stereomicroscope and matched them by size. This common microscopic analysis is based on individual islet sizing, calculation of the frequency distribution, and conversion into an islet equivalent (IEQ), which is the volume of a spherical islet with a diameter of 150 mm ( 27 ). On the following day, 20 IEQs were incubated in 2 ml of RPMI-1640 media with 5 mM or 16.7 mM glucose.…”
Section: Islets Isolation and Insulin Secretionmentioning
confidence: 99%